Senior centres in Pahang: an ethnographic study - Kuiper, Matthew; Ibrahim, Rahimah; Singh, Sarjit; Che Hasan, Muhammad Kamil (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Senior centres are a beneficial social tool to promote well-being and decrease social isolation. The Malaysian government financially supports centres for ageing participants to use. Centres provide social support, humanitarian projects, opportunities to share life stories, and education. Although there are many benefits, a study in Terengganu found that many older people are not familiar with the programs at the centre and among those who are aware only a small percentage attend. This study will assess the programming offered by local leadership through semi-formal interviews and use rapid assessment procedures to evaluate the perceptions of ageing people concerning community centres.